Characteristics and Substrate Specificity of Semi-Purified Bacterial Protease of Bacillus thuringiensis HSFI-12 with Potential as Antithrombotic Agent - Dina Ferdiani; Dewi Seswita Zilda; Muhammad Ardi Afriansyah; Stalis Norma Ethica (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Commercial proteases, such as Nattokinase (NK), Staphylokinase (SAK), and Streptokinase (SK) play an important role in the destruction of thrombus, the main cause of death in cardiovascular disease. The latest technology combining enzymes with certain drugs is the target of new research in the thrombolytic area. The first step is to develop protease from Bacillus thuringiensis HSFI-12 bacteria as an antithrombotic agent, characterization of the bacterial enzyme is necessary. This study aims to determine the specificity of protease from Bacillus thuringiensis HSFI-12 to explore its potential as an antithrombotic agent in terms of anticoagulant and fibrinolytic activities. The molecular weight and specificity of bacterial protease were determined with a zymographic method with casein as substrate. Bacillus thuringiensis HSFI-12 was first cultured on Nutrient Agar (NA) media and then on Skim Milk Agar (SMA) media. The obtained crude protease from Skim Milk Broth (SMB) was then concentrated as dialysate. Both crude and dialysate proteases were tested for their specific activity, as well as anticoagulant and fibrinolytic activities. Next, the dialysate’s molecular weight and specificity on the casein substrate were investigated using the zymographic method. As result, protease activity in crude form is lower than that in dialysate, which was 0.5570 ± 0,004 U/mL and 2.1767 ± 0,005 U/mL, respectively. The molecular weight of the obtained bacterial protease was between 117 – 133 kDa and the enzyme is capable of degrading casein as shown on the zymogram. Overall, both crude and dialysate proteases of Bacillus thuringiensis HSFI-12 show potential as an antithrombotic agent for exhibiting anticoagulant and antiplatelet activities. Yet, it could not exhibit direct fibrinolytic activity implying the possibility that the enzyme plays a role as a plasminogen activator, which can dissolve fibrin by activating plasmin.